2021
DOI: 10.1016/j.bioelechem.2020.107671
|View full text |Cite
|
Sign up to set email alerts
|

An advanced molecularly imprinted electrochemical sensor for the highly sensitive and selective detection and determination of Human IgG

Abstract: Graphical abstract Schematic 1 Electrochemical determination of human IgG using CuFe 2 O 4 nanospheres molecularly imprinted polymers modified with MoS 2 @N-GQDs-IL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 77 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…In particular, the linear range of the PPE sensor extends to 2 orders of magnitude lower concentrations than the other sensors, which is a record sensitivity at low concentrations for an EIS-based IgG sensor. These research results indicate that PPE-based EIS sensors have highly reproducible and ultrasensitive characteristics. …”
Section: Resultsmentioning
confidence: 70%
“…In particular, the linear range of the PPE sensor extends to 2 orders of magnitude lower concentrations than the other sensors, which is a record sensitivity at low concentrations for an EIS-based IgG sensor. These research results indicate that PPE-based EIS sensors have highly reproducible and ultrasensitive characteristics. …”
Section: Resultsmentioning
confidence: 70%
“…Electrochemical biosensing has an enormous impact on the biosensing of IgG, and a broad range of studies have been conducted to attain the unique, selective, sensitive, and economical characteristics of a biosensor. Liang et al, has reported a molecular imprinted electrochemical biosensor for selective and extremely sensitive detection of IgG [ 57 ]. The GCE (glassy carbon electrode) was modified using a MoS2@N-GQDs-IL (molybdenum disulfide @nitrogen-doped graphene quantum dots with ionic liquid) nanocomposite.…”
Section: Biosensors For the Detection Of Iggmentioning
confidence: 99%
“…Significantly, with relatively low conductivity, it needs to accommodate additional nanomaterials to be operational [ 74 ]. Axin Liang et al [ 75 ] modified GCE with highly conductive MoS 2 @N-GQDs-IL to magnify electrochemical signals for human immunoglobulin G (IgG). MoS 2 was functionalized with nitrogen-doped GQDs (N-GQDs).…”
Section: Applications Of Nanomaterials In Mip Sensorsmentioning
confidence: 99%